The Role of The Structural Factor in The Land Value Spatial Model : A Case Study of Surabaya City, Indonesia - Oetomo, Hening Widi (Rekayasa, 2008)
Theinstillation of GIS in the land property evaluation sector in Indonesia, is still at its early stage. Theproperty taxation department has been using GIS in producing property taxation data since 1996, its main task being suppl ying computer-generated maps (Dirjen Cukai, 1998). Spatial analysis which is the strength of GIS remains to be practised. The land value spatial model is a model that assesses the value of land based on spatial treatments which have been identified as influencing thevalue of land. Generally there are 4 treatments influencing thevalue of land i.e. the structural factor, the neighbourhood factor, the location factor and the timefactor. Spatial analysis is needed toproduce mapsfrom these treatments inorder tochurn out spatial data. Thespatial analysis inneed are reclassification, overlapping, length and distance measurement, neighbourhood and network analysis. Furthermore, statistical analysis is needed toform a spatial model. This studyfocuses on a solefactor that is the stuctural factor in influencing the value of land. Thestructural factor includes both physical and land usage treatments. Thephysical factor to be included in this study are the area, thefront width, the direction and the shape.. There are 148 land transaction lots used inshaping the spatial model. This working paper attempts toexamine the level of influence of the physical treatments on the land value in the area studied.